2020
DOI: 10.1016/j.crfs.2020.09.001
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: Studies on survivability, storage stability of encapsulated spray dried probiotic powder

Abstract: Awareness about probiotic food and their health benefits is increasing tremendously. However, probiotics have to withstand the harsh conditions that come across during their processing, handling, storage, and gastrointestinal conditions. Encapsulating technologies can be used to protect the probiotics during their passage through the gastrointestinal system of the human gut. Probiotics as an ingredient in dry powder form can be easily handled, stored, and used in developing the probiotic functional products. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 44 publications
3
25
0
Order By: Relevance
“…Also, they noticed that after 10 weeks of storage the amount of bacteria decreased from 71-93 to 50-30%. Single probiotic cultivars were encapsulated with MD or its mixture with GA at similar inlet air temperature (130-150°C), and a high survival of bacteria was observed (Arepally & Goswami, 2019;Arepally et al, 2020). However, the authors used water medium not juice medium with lowered pH, like in our experiments.…”
Section: Microbiological Analysismentioning
confidence: 96%
See 2 more Smart Citations
“…Also, they noticed that after 10 weeks of storage the amount of bacteria decreased from 71-93 to 50-30%. Single probiotic cultivars were encapsulated with MD or its mixture with GA at similar inlet air temperature (130-150°C), and a high survival of bacteria was observed (Arepally & Goswami, 2019;Arepally et al, 2020). However, the authors used water medium not juice medium with lowered pH, like in our experiments.…”
Section: Microbiological Analysismentioning
confidence: 96%
“…Gum Arabic (GA) is known from its inhibits dehydration of cellular components and protection of microbial cells during drying and storage. At the same time, gum Arabic significantly increases the glass transition temperature and reduces hygroscopicity and caking (Arepally et al, 2020;Zhang et al, 2020a;Zhang et al, 2020b).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Currently, the food industry has been interested in developing new functional food products concerned about nutrition and foods with probiotics that stand out in the market. For probiotics to be therapeutically effective, it has been suggested that products should contain at least 6 log CFU/g of bacteria up to the end of its shelf life, and it is recommended that probiotic food should contain a minimum of 10 8 CFU per gram or milliliter at the time of consumption [4]. However, most probiotics are sensitive and easily lose their viability when exposed in stressful conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Microencapsulation is the process of encapsulating substances with a state of solids, liquids, and gases with polymers or coating material to form small capsules. Among the several microencapsulation techniques, spray drying is a commonly used method due to its low energy consumption, less cost, higher production efficiency, storage and appears to be a good alternative for large-scale production of probiotic powders [4,7]. Although, during the spray drying process, the membrane of probiotics cells may get damaged from dehydration and thermal stress that may cause a reduction in bacterial cell survival [6,8].…”
Section: Introductionmentioning
confidence: 99%